Families affected by deafness: hospital services uptake in a multiethnic population. Issue 5 (25th April 2005) - Yoong, S Y; Feltbower, R; Spencer, N; McKinney, P A
Abstract : Aims: To examine the uptake of relevant hospital services by families with deaf children and to compare use of these services between Pakistani and white families. Methods: A total of 214 deaf children with amplification aids who attended their paediatric outpatient and school medical appointments from October 2000 to March 2003 were studied in an observational cohort study. Results: The demographic profile of both the Pakistani and white families was similar. Pakistani children had a statistically significant excess of the following risk factors: consanguineous marriages (86.4% Pakistani, 1.5% white), family history of deafness (66.4% Pakistani, 38.8% white), and family size (birth order >5: 12.8% Pakistani: 4.5% white). White children were more likely to have had post-meningitis deafness (1.4% Pakistani, 13.4% white) and congenital infections, or have dysmorphic features (5.0% Pakistani, 13.4% white). Overall the uptake of relevant hospital services by Pakistani and white families was very similar irrespective of an early or late diagnosis. There was an increased likelihood of white families declining cochlear implantation (17.6% Pakistani, 75.0% white). Conclusions: This study did not show significant differences in hospital service uptake despite different risk profiles for childhood deafness for both Pakistani and white families in Bradford. Among specialist services offered, cochlear implantation was more likely to be accessed by Pakistani families.